2018
DOI: 10.1109/jqe.2018.2822179
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lateral Scaling Impact on the Frequency Performance of SiGe Heterojunction Bipolar Phototransistor

Abstract: The influence of the lateral scaling such as emitter width and length on the frequency behavior of SiGe bipolar transistor is experimentally studied. Electrical transistors of different emitter sizes are designed and fabricated by using a commercial bipolar transistor technology. The effect of peripheral current and collector current spreading on electrical bipolar transistor performances are analyzed in regards to the state of the art. Furthermore, the lateral scaling effect on SiGe phototransistor electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Moutier et al [2] identified the fastest and slowest regions of the HPT structure based on physical simulations. The lateral dimensioning effects such as the peripheral and twodimensional carrier flows are studied in [5]. In [6,7], the phototransistor performances are investigated through optoelectronic compact circuit modelling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moutier et al [2] identified the fastest and slowest regions of the HPT structure based on physical simulations. The lateral dimensioning effects such as the peripheral and twodimensional carrier flows are studied in [5]. In [6,7], the phototransistor performances are investigated through optoelectronic compact circuit modelling.…”
mentioning
confidence: 99%
“…20 Ω•cm. The detailed schematic and specifications of the bipolar transistor technology used are the same as presented in [5,10,11]. The HPT fabrication does not modify the vertical stacks of layers of the standard bipolar transistor (HBT) technology.…”
mentioning
confidence: 99%